2011
DOI: 10.1111/j.1360-0443.2011.03380.x
|View full text |Cite
|
Sign up to set email alerts
|

Addiction Research Centres and the Nurturing of Creativity. National Institute on Alcohol and Drugs Policies, Brazil

Abstract: The National Institute of Public Policy for Alcohol and Other Drugs (INPAD) is based at the Federal University of São Paulo, Brazil, and was created to collect scientific evidence regarding epidemiology, develop new therapeutic approaches, study health economics and provide education to subsidize the proper measures to change the Brazilian scenario of alcohol and drug consumption. Policies directed towards the control of alcohol and drugs in Brazil are fragmented, poorly enforced and therefore ineffective. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A previous study showed that the 2008 policy implementation in Brazil (drunk driving) had a significant impact on reduction of traffic injuries and fatalities [30]. Other studies conducted in Brazil have emphasized comprehensive and effective alcohol and drug policy [11] since so far policies have been fragmented and poorly enforced [31]. As shown by our results, the alcohol consumption and the attributable disease burden mirror each other and the implemented policies fit the trend of the decreasing disease burden.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that the 2008 policy implementation in Brazil (drunk driving) had a significant impact on reduction of traffic injuries and fatalities [30]. Other studies conducted in Brazil have emphasized comprehensive and effective alcohol and drug policy [11] since so far policies have been fragmented and poorly enforced [31]. As shown by our results, the alcohol consumption and the attributable disease burden mirror each other and the implemented policies fit the trend of the decreasing disease burden.…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol consumption by most women in this study converges with data from the World Health Organization (14) , when it states that alcohol consumption by women has grown in several countries and has been approaching that of men who historically have always been greater. In Brazil, an epidemiological study has shown that alcohol consumption by women has grown linearly (15) .…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of alcohol use among Brazilian students in all the cities studied points that many gaps remain to be filled for a comprehensive antialcohol policy. According to Laranjeira and Mistushiro, 18 the unregulated market of alcohol in Brazil has contributed to the worsening health of the Brazilian population in the past decades, supporting the position of alcohol misuse as one of the major public health problems in Brazil. One of the hypothesis to explain the unregulated alcohol market, even considering the existence of some laws that aim to regulate alcohol sales and purchase, is that Brazil is home of one of the largest breweries in the world – Companhia de Bebidas das Américas (AMBEV) –, which has a strong political influence on the Country.…”
Section: Discussionmentioning
confidence: 99%